Contested identities : Belhar, Elsies River and Mitchell’s Plain community ideas of queer ‘Colouredness’ - Lunde, Kerenza (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.